The atrocity of hunger : starvation in the Warsaw, Łódź, and Kraków ghettos during World War II - Sinnreich, Helene Julia (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2023)
During World War II, the Germans put the Jews in Nazi-occupied Poland into ghettos which restricted their movement and, most crucially for their survival, access to food. The Germans saw the Jews as 'useless eaters,' and denied them sufficient food for survival. The hunger which resulted from this intentional starvation impacted every aspect of Jewish life inside the ghettos. This book focuses on the Jews in the Łódź, Warsaw, and Kraków ghettos as they struggled to survive the deadly Nazi ghetto and, in particular, the genocidal famine conditions. Jews had no control over Nazi food policy but they attempted to survive the deadly conditions of Nazi ghettoization through a range of coping mechanisms and survival strategies. In this book, Helene Sinnreich explores their story, drawing from diaries and first-hand accounts of the victims and survivors. This title is also available as Open Access on Cambridge Core.
The Nazi Invasion: Violence, Displacement, and Expropriation -- Jewish Leadership -- The Supply and Distribution of Food: Strategies and Priorities -- The Physical, Mental, and Social Effects of Hunger -- Hunger and Everyday Life in the Ghetto -- Socioeconomic Status and Food Access -- Relief Systems and Charity -- Illicit Food Access: Smuggling, Theft, and the Black Market -- Labor and Food in the Ghettos -- Deportations and the End of the Ghettos.
Title from publisher's bibliographic system (viewed on 09 Feb 2023).
Keywords: Holocaust, Jewish (1939-1945) -- Poland; War and society -- Poland -- History -- 20th century; Starvation -- Poland -- History -- 20th century; World War, 1939-1945 -- Atrocities -- Poland; World War, 1939-1945 -- Food supply -- Poland; Jewish ghettos -- Poland -- Łódź -- History -- 20th century; Jewish ghettos -- Poland -- Warsaw -- History -- 20th century; Jewish ghettos -- Poland -- Łódź -- History -- 20th century